P04.20 Analysis of HORMAD1, FTHL17 and ADAM29 Cancer/testis specific genes expression in Glioblastoma. (19th September 2018) - Anvari, K; Mojarrad, M; Gholamin, M; Fathi, M; Tabatabaii, A; Eslahi, A
Abstract: Background: Glioblastoma multiform (GBM, World Health Organization grade IV) is the most common and aggressive primary brain tumor.Immunotherapy is a promising therapeutic adjuvant in fighting against this cancer. Cancer/testis antigens (CTAs) are a group of tumor-associated antigens that are typically restricted to adult testis, but they are aberrantly expressed in several types of cancers, especially in advanced cancers with stem-like characteristics. These tumor-associated antigens are immunogenic in different cancers. Finding of frequently expressed CTAs in GBM can provide effective immunotherapeutic targets to use in translational researches on this cancer. The aim of this study was conduct an extensive expression analysis of ADAM29, HORMAD1, FTHL17 in GBM to determine whether these antigens can be appropriate target in immunotherapy of GBM. Material and Methods: Fifty pathologically confirmed GBM paraffin embedded tissue sample were conducted into this experiment. Total RNA was extracted from these samples and TaqMan based RealTime PCR technology was used to evaluation of HORMAD, ADAM29 and FTHL17 gene expression Results: according to our results HORMAD1 is the most frequent expressed gene in these tissue samples. Forty-four percent of samples (22 out of 50 samples) expressed HORMAD1 in various levels. Either FTHL17 and ADAM29 were expressed in only one of samples.On the other hand, according to statistical studies of patients' demographic findings and the expression of genes, HORMAD1 has had a much higher level of expression in glioblastoma samples than other genes, which, based on these results, we can consider this gene as a therapeutic target in immunotherapy. Conclusion: CT46/HORMAD1 is a single-copy gene on chromosome 1q21.3, A review of carcinoma showed that 31% of carcinomas express this antigen in high numbers. In 2006, the gene had a high expression in gastric cance. so far no precise and thorough study has been done on the existence (expression) of these gene in glioblastma samples, HORMAD1 can be a promising target in immunotherapy research targeting GBM.